Galileo Galilei At the Threshold of the Scientific Age - Osterhage, Wolfgang W. (Springer Biographies,, 2018)
This new scientific biography of Galileo explores the influences on, and of, his exceptional work, thereby revealing novel connections with the worldviews of his age and beyond. Galileo Galilei's contribution to science is unquestionable. And his conflict with the church establishment of his time is no less famous. In this book, authored by a physicist and history scholar, Galileo's life and work are described against a backdrop of the prior scientific state of the art in his various fields of achievement. Particular emphasis is placed on Galileo's vision of the world in relation to historic and also future cosmological models. The impact of his discoveries and theories for the later development of physics and astronomy is a further focus of the narrative.